Prevalence and risk factors of diarrhea morbidity among under-five children in India: A systematic review and meta-analysis - Ganguly, Enakshi; Sharma, Pawan K; Bunker, Clareann H (Indian Journal of Child Health, 2015)
Background: Acute diarrhea accounts for a huge burden of infectious diseases in under-five children. Objective: This systematic review was carried out to study the prevalence and associated risk factors of diarrhea among Indian children aged